Effects of processing parameters on arc stability and cutting quality in underwater wet flux-cored arc cutting at shallow water. (June 2018) - Liu, Duo; Li, HongLiang; Yan, YaoTian; Guo, Ning; Song, XiaoGuo; Feng, JiCai
Abstract: Arc stability and cutting quality of flux-cored arc cutting (FCAC) process were characterized using gas-forming wire and exothermic wire. The measured values of voltage and current fluctuated greatly during cutting process. Arc extinction phenomena was very common for underwater FCAC process. The variation coefficient of arc voltage and the form of arc voltage histogram were the best indicators to evaluate cutting process. Gas-forming wire and exothermic wire functioned differently in FCAC process. With increasing arc voltage, cutting process became unstable while cutting quality was improved. An increase in wire feeding speed would increase the consumption of wires, and the high proportion of arc extinction decreased the stability of the cutting process. Low cutting speed would deteriorate cutting arc stability. Successful cut could be achieved at all investigated cutting parameters. Cutting quality were evaluated using indexes include cut width, cut bevel angle, cut edges straightness, bridging degree and residual metal on the backside of the cut.